2012
DOI: 10.17925/enr.2013.08.01.27
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Seizures in Patients with Lacunar Strokes

Abstract: Abstractlacunar strokes are mainly related to cerebral microangiopathy and to the presence of leukoaraiosis. cognitive impairment is frequently linked to the presence of lacunes and white matter changes. The cognitive impairment consists mainly of disturbances of executive functions sometimes leading to dementia. it is mainly due to interruption of the frontal-subcortical neuronal circuits. Seizures are also observed in patients with lacunes and white matter changes. although lacunes cannot be considered as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The authors speculate that some subcortical white matter lesions may also affect U‐fibers, leading to a higher propensity for seizures. De Reuck and Van Maele investigated the amount of cognitive decline in 292 patients with leukoaraiosis, with and without seizures (n = 44 and 248, respectively), and found a higher proportion and severity of cognitive decline in patients with seizures. These authors speculated that an underlying neurodegenerative disease, rather than leukoaraiosis, might cause epilepsy in those patients.…”
Section: Resultsmentioning
confidence: 99%
“…The authors speculate that some subcortical white matter lesions may also affect U‐fibers, leading to a higher propensity for seizures. De Reuck and Van Maele investigated the amount of cognitive decline in 292 patients with leukoaraiosis, with and without seizures (n = 44 and 248, respectively), and found a higher proportion and severity of cognitive decline in patients with seizures. These authors speculated that an underlying neurodegenerative disease, rather than leukoaraiosis, might cause epilepsy in those patients.…”
Section: Resultsmentioning
confidence: 99%
“…The first study [52] found that neither the presence of vascular risk factors including hypertension, nor the degree of white matter changes were associated with the development of epilepsy. The second study [53] on 292 subjects with lacunar strokes found that 44 patients with seizures had a lower main National Institute of Health Stroke Scale score (p = 0.00133) and a lower Mini Mental State Examination score (p < 0.001) as compared to 248 patients without seizures. These authors conclude that the seizures were more linked to the cognitive status than to SVD, postulating that an underlying neurodegenerative process may be responsible for seizures and cognitive impairment.…”
Section: Seizures Associated With Small Vessel Diseasementioning
confidence: 98%
“…However, about half of the patients included in the study did not undergo brain MRI, thus limiting the generalizability of results. Two retrospective studies with overlapping population [52,53] examined the incidence and predictors of seizures and epilepsy in patients with lacunar stroke. The first study [52] found that neither the presence of vascular risk factors including hypertension, nor the degree of white matter changes were associated with the development of epilepsy.…”
Section: Seizures Associated With Small Vessel Diseasementioning
confidence: 99%